HUBUNGAN PENGETAHUAN PEMELIHARAAN KESEHATAN GIGI TERHADAP KONDISI INDEKS OHIS PADA SISWA DIKTUBA SPN POLDA KALSEL - Muhammad Arya Danendra; R. Harry Dharmawan Setyawardhana; Diana Wibowo; Ika Kusuma Wardani; Renie Kumala Dewi (Universitas Lambung Mangkurat, 2024)
Background: Dental and oral health problems in Indonesia are quite high based on the 2018 Riskesdas data. According to Blum's theory, the high number of dental and oral health problems can be caused by four main factors which include behavior, environment, health services and heredity which are based on a lack of knowledge about the importance of maintaining dental and oral health. Objective: This study aims to analyze the relationship of knowledge about maintaining dental health and oral hygiene conditions in students of the SPN Polda South Kalimantan dictuba. Methods: This research is an analytic observational study with a cross sectional approach. The sampling technique used simple random sampling with a total sample of 35 people. Test analysis using the SPSS application with the somers'd method. Results: The results of the study showed that knowledge of dental and oral health was a good level of knowledge and the OHIS index was included in the good category. Conclusion: There is a significant relationship between the knowledge of dental health maintenance with the OHIS index on students of the South Kalimantan Regional Police SPN Diktaba.Keywords : Knowledge, Maintenence, OHIS, Police